Penggunaan Multimedia Interaktif Sebagai Pemenuhan Kebutuhan Belajar Pendidikan Agama Islam Dalam Ranah Kognitif Pada Anak Tunagrahita - Maria, Anly; Aini, Ai Sri Qurotal (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
Children who have limitations in development or are born with physical or non-physical deficiencies are considered abnormal people. One of them is a child with a disability, they have intellectual retardation. Many people around think that these children do not need to learn and worship. In contrast, the Islamic view of humans is only seen from faith. To get faith in accordance with the rules that Allah has determined. The purpose of this study is to describe the use of interactive multimedia in meeting the needs of learning Islamic religion in the cognitive domain in children with disabilities. Researchers used a qualitative approach with a case study type of research.  Data analysis techniques through data reduction, data presentation, and conclusion drawing. The results showed that the fulfillment of Islamic learning needs by using interactive multimedia can meet the cognitive learning needs of the knowledge and understanding level, namely knowing and understanding the names and duties of angels by pairing the names and duties of the appropriate angels in completing the fuzzle game.  Keywords: Interactive Multimedia, Learning Needs, PAI, Cognitive.